Research on a Micro Piezoelectric Gyroscope with Concentrated Rocking‐Mass. (23rd March 2015) - Cheng, Yuxiang; Zhang, Weiping; Tang, Jian; Liu, Wu; Wang, Yinghai; Chen, Wenyuan
Abstract : This study introduces a Micro Electro Mechanical Systems (MEMS) piezoelectric gyroscope with a concentrated rocking‐mass, made from PZT ceramic. The gyroscope operates in the rocking mode with a frequency of 91.3 kHz. This gyroscope follows the study of the MEMS piezoelectric BAW gyroscope with an improvement of fewer boundary constraints, which enhances the device's operability and characteristic. Through the MEMS fabrication process, the device with a side of length 12 mm achieves a rate sensitivity of 30.7 μV/°/s and a bias stability of 8.6°/s. This study describes the design, fabrication, circuit system, and characteristics of this micro piezoelectric gyroscope.